Pelatihan Pembuatan Podcast Sebagai Media Komunikasi Berbasis Teknologi Informasi Dan Komunikasi Pada IPNU Ciledug - Asriyani Sagiyanto; Liliyana; Achmad Syahlani; Ferari Lancia (Prisani Cendekia, 2022)
Utilization of Information Communication Technology encourages the formation of communities that are interconnected by using the internet network to communicate and carry out various activities. One aspect of change due to the increasing use of the internet is communication media. The need for ICT-based communication media is also felt by the Ciledug Nahdlatul Ulama Student Association (IPNU). IPNU is an autonomous body of Nahdlatul Ulama based on students, students, and santri, as a forum for fostering the next generation of scholars and successors of the nation's struggle. Because IPNU is an organization whose members are generations of Y and Z, and the problems faced by IPNU Ciledug, relating to communication media are to disseminate content related to their organization, a communication media that is appropriate to that generation is needed. The solution offered to solve these problems is through this community service activity, namely providing training on making Podcasts as an ICT-based communication medium to IPNU Ciledug members. The implementation of this community service activity consists of 3 stages, namely; The preparation stage, to identify problems, apply for permits to the IPNU Ciledug management, and make preparations for the implementation of training on making podcasts; The implementation stage of the Podcast making training; and the activity evaluation stage, by giving a questionnaire to the training participants to find out how they responded to this community service activity.